Analisis Perbandingan Tingkat Stress Mahasiswa Saintek dan Soshum dalam Pembelajaran Daring pada Masa Pandemi Covid-19 Berbasis Internet of Things - Erika Maulidiya; Iftihatul Aulia Rahmah; Putri Ridha Amalia; Ryan Ramel; siti sheilawati; Muhammad Alkaff (Teknik Informatika Universitas Pamulang, 2021)
The spread of COVID-19 has occurred in 2019, which has had an enormous impact on the world's population. The continuous spread of COVID-19 has caused several countries to reduce the transmission of COVID-19, one of which is implementing online learning at schools and universities. The impact that occurs on students due to home study policies makes some students feel anxious and depressed. There are two study groups at the University of Lambung Mangkurat, namely the Social Humanities (Soshum) and Science and Technology (Saintek). The student who majored in science, technology, and social science has a different way of finding the information needed and understanding every material available online. This problem is due to cultural differences in the applied learning system. These differences certainly cause different stress levels for each student majoring in science, technology, and social sciences. Therefore, this study was conducted to determine the difference in stress levels experienced by Lambung Mangkurat University students in science, technology, and social media while online. This study uses two stages to compare the results of student stress levels, including filling out the DASS42 questionnaire and direct testing with 3 IoT sensors, namely GSR, body temperature (GY-906 MLX90614 Infrared Temperature Sensor), and pulse rate (MAX30102 Pulse Oximeter & Heart-Rate Sensor). The application of the Fuzzy Logic method is used as a parameter measurement when measuring IoT-based stress levels.